Synthesis, Characterization and Biological Properties of Mn(II), Co(II), Ni(II) and Cu(II) Chelates of Some Schiff Bases Containing N-S-O and N-O-O Moiety - Chowdhary, Vimla; Sharma, Anju; Sharma, Shobha (Asian Journal of Chemistry, 2010)
Metal chelates of bivalent transition metal ions have been synthesized by the reaction of o-(N-α-thiophene-2-aldimino)phenol (HTP), o-{N-α-furfuraldimino)phenol (HFP) and o-(N-benzofuran-2-yl methylimino) benzene sulphonic acid (HBB) with corresponding metal(II) acetate. The complexes have been characterized on the basis of their elemental analysis, potentiometeric studies, conductance measurement and spectral analysis. The complexes have been screened for their biocidal activities against bacteria Staphylococcus aureus, Escherichia coli, Bacillus subtilis and Streptococcus pyogenes and fungi Aspergillus niger, Draschelera australiensis and Helminthosporium oryzae. The metal chelates were found to be potent antimicrobial agents compared to the ligands.